A Perspective on the 2023 Cholera Outbreaks in Zimbabwe: Implications, Response Strategies, and Policy Recommendations - Gbolahan Olatunji; Emmanuel Kokori; Abdulrahmon Moradeyo; Doyin Olatunji; Folake Ajibola; Oluwaseun Otolorin; Nicholas Aderinto (Springer, 2023)
Abstract Cholera continues to severely threaten public health, particularly in regions with inadequate access to clean water and sanitation. Zimbabwe, a southern African nation, has witnessed recurrent cholera outbreaks, highlighting the enduring vulnerabilities faced by communities grappling with these underlying challenges. The 2023 cholera outbreak in Chegutu resulted in a devastating impact, with approximately 100 reported deaths and nearly 5000 confirmed and suspected cases. Beyond its immediate health consequences, the outbreak has strained the already fragile healthcare system, exacerbated issues of malnutrition, and disrupted education, particularly affecting vulnerable populations. The Zimbabwean government, non-governmental organisations (NGOs), and international agencies have initiated comprehensive efforts to combat the outbreak, encompassing medical treatment, surveillance, public health measures, infrastructure improvement, and community empowerment. Policy recommendations and future directions are discussed, emphasising risk communication, stakeholder engagement, standardisation, evaluation, resource allocation, and capacity-building to bolster prevention and control measures.